Army Seeks Info On Patriot-Interface Kits For Networked Missile Defense - Doubleday, Justin (Inside the Pentagon's Inside the Army, 2014)
Successful development and production of the Patriot interface kits could affect the export potential of the IAMD battle command system. Since 2012, the software, developed by Northrop Grumman, has been a part of the Pentagon's Defense Exportability Features initiative, which aims to address security concerns normally prohibiting foreign sales early in program development.